Vegetation and Climate Change in Southwestern Australia During the Last Glacial Maximum. Issue 3 (13th February 2019) - Sniderman, J. M. K.; Hellstrom, J.; Woodhead, J. D.; Drysdale, R. N.; Bajo, P.; Archer, M.; Hatcher, L.
Abstract: The nature and duration of the Last Glacial Maximum (LGM) in Australia are poorly understood, with little regional agreement on the timing and direction of LGM climate changes. One reason for this is that Australian Late Pleistocene terrestrial sediments typically are both sparse and inorganic, inhibiting the development of detailed radiocarbon chronologies. To address this problem, we extracted fossil pollen from radiometrically dated stalagmites collected in southwest Western Australia. Our pollen record, supported by 30 U‐Th dates, reveals the vegetation response to Late Pleistocene climates between ~34 and 14 ka, through the body of the LGM. Before ~28 ka, sclerophyll forests were more open than today, but at ~28 ka forest cover was essentially eliminated, and treeless conditions were maintained until progressive reforestation at ~17.5 ka. This ~10‐ka‐long full glacial episode correlates with other mid‐high latitude Southern Hemisphere records, suggesting that LGM environmental changes were closely coordinated across the hemisphere. Plain Language Summary: This study uses fossil pollen extracted from radiometrically dated stalagmites to document detailed vegetation and climate changes that occurred in the southwest of Western Australia at the peak of the last ice age. Today this region is the only part of southwest Western Australia that supports forests, yet for approximately 10, 000 years between 28, 000 and 18, 000 years ago, eucalypt strongholds collapsed and the dominant vegetation type appears to have been shrublands. The timing and duration of full glacial conditions in southwest Australia are very similar to patterns of glacial environmental change observed in other mid‐high latitude regions of the Southern Hemisphere. Key Points: U‐Th dated speleothem palynology illustrates the timing and duration of the Last Glacial Maximum (LGM) in Western Australia Between 28 and 18 ka, the forested far southwest of Western Australia was essentially a treeless shrubland The pattern of LGM climate change is coherent with records from other mid‐high latitude Southern Hemisphere regions